2020
DOI: 10.1080/20008198.2020.1810903
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of common and stress-related mental health disorders in healthcare workers based in pandemic-affected hospitals: a rapid systematic review and meta-analysis

Abstract: Stedman (2020) The prevalence of common and stress-related mental health disorders in healthcare workers based in pandemic-affected hospitals: a rapid systematic review and meta-analysis,

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
69
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 46 publications
(88 reference statements)
5
69
0
1
Order By: Relevance
“…While Pappa et al studied the prevalence of depression, anxiety, and insomnia among HCPs during the COVID-19 outbreak [ 27 ], Allan et al investigated the prevalence of common and stress-related mental health disorders in healthcare workers based in pandemic-affected hospitals [ 28 ]. Compared to Allan et al’s meta-analysis [ 28 ], we limited our results to the SARS studies reporting odds ratios, while others did not [ 29 , 30 , 31 , 32 , 33 , 34 ] or had too small a sample size for regression analysis [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…While Pappa et al studied the prevalence of depression, anxiety, and insomnia among HCPs during the COVID-19 outbreak [ 27 ], Allan et al investigated the prevalence of common and stress-related mental health disorders in healthcare workers based in pandemic-affected hospitals [ 28 ]. Compared to Allan et al’s meta-analysis [ 28 ], we limited our results to the SARS studies reporting odds ratios, while others did not [ 29 , 30 , 31 , 32 , 33 , 34 ] or had too small a sample size for regression analysis [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, an examination of the levels of PTSD, anxiety, and depression symptoms among the study groups have revealed that dentists (who hold MD degrees), in contrast to other dental HCWs, had significantly higher PSS-SR re-experiencing, arousal, intrusions, and total scores, while dental assistants (persons without an MD degree), in contrast to other participants, had significantly higher IES-R avoidance scores. This is somewhat interesting, because nurses (which is the closest analog to dental assistant in general medicine) typically reported higher levels of symptoms and distress than doctors [ 3 , 6 , 8 , 52 ], with a few studies reporting no difference [ 53 , 54 ] and only one study reporting higher rates in doctors [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…During a pandemic, frontline HSCWs are at increased risk of infection while also dealing with working conditions that are more difficult and demanding than usual 3 . Studies have shown that working in healthcare roles during epidemics and pandemics such as SARS, MERS, and Ebola disease, was associated with PTSD, depression, anxiety, and other mental health disorders 9-12 . Research conducted during previous pandemics has also highlighted potential risk factors, including being tasked to directly work with patients suspected of having the virus 13-16 , working as a nurse 4 9 10 17 18 , being younger 16 , being the parents of dependent children 16 and being a woman 19 .…”
Section: Introductionmentioning
confidence: 99%